Zhishi Daozhi decoction alleviates constipation induced by a high-fat and high-protein diet via regulating intestinal mucosal microbiota and oxidative stress - Peng, Xinxin; Yi, Xin; Deng, Na; Liu, Jing; Tan, Zhoujin; Cai, Ying (Frontiers in Microbiology, 2023)
Background: Growing evidence has demonstrated that a high-fat and high-protein diet (HFHPD) triggers constipation. The study on the intestinal microecology mechanism of Zhishi Daozhi decoction (ZDD) will provide clinical strategies for alleviating the constipation side effects of HFHPD. Materials and methods: The mice were randomly divided into five groups, normal group (MN), natural recovery group (MR), low-dose ZDD group (MLD), medium-dose ZDD group (MMD), and high-dose ZDD group (MHD). After the constipation model was established by HFHPD combined with loperamide hydrochloride (LOP), different doses of ZDD were used for intervention. Subsequently, the contents of cholecystokinin (CCK) and calcitonin gene-related peptide (CGRP) in serum, superoxide dismutase (SOD) and malondialdehyde (MDA) in liver were determined. The DNA of intestinal mucosa was extracted and 16S rRNA amplicon sequencing was used to analyze the changes of intestinal mucosal microbiota. Results: After ZDD treatment, CCK content in MR decreased and CGRP content increased, but the changes were not significant. In addition, the SOD content in MR was significantly lower than in MLD, MMD, and MHD, and the MDA content in MR was significantly higher than in MN, MLD, and MHD. Constipation modeling and the intervention of ZDD changed the structure of intestinal mucosal microbiota. In constipation induced by HFHPD, the relative abundance of pathogenic bacteria such as Aerococcus, Staphylococcus, Corynebacterium, Desulfovibrio, Clostridium, and Prevotella were increased. After the intervention of ZDD, the relative abundance of these pathogenic bacteria decreased. The relative abundance of Candidatus Arthromitus and the abundance of Tropane, piperidine and pyridine alkaloid biosynthesis pathways were both increased in MHD. Conclusion: Constipation induced by HFHPD can increase pathogenic bacteria in the intestinal mucosa, while ZDD can effectively relieve constipation, reduce the relative abundance of pathogenic bacteria and alleviate oxidative stress injury. In addition, high-dose ZDD can increase the abundance of beneficial bacteria, which is more conducive to the treatment of constipation.